Phase Control of Cs‐Pb‐Br Derivatives to Suppress 0D Cs4PbBr6 for High‐Efficiency and Stable All‐Inorganic CsPbBr3 Perovskite Solar Cells. Issue 8 (12th December 2021) - Zhu, Jingwei; He, Benlin; Yao, Xinpeng; Chen, Haiyan; Duan, Yanyan; Duan, Jialong; Tang, Qunwei
Abstract: The precise phase control of Cs‐Pb‐Br derivatives from 3D CsPbBr3 to 0D Cs4 PbBr6 highly determines the photovoltaic performance of all‐inorganic CsPbBr3 perovskite solar cells (PSCs). Herein, the preferred phase conversion from precursor to Cs‐Pb‐Br derivatives is revealed by theoretically calculating the Gibbs free energies (∆ G ) of various phase conversion processes, allowing for a simplified multi‐step solution‐processable spin‐coating method to hinder the formation of detrimental 0D Cs4 PbBr6 phase and enhance the photovoltaic performance of a PSC because of its large exciton binding energy, which is regarded as a recombination center. By further accelerating the interfacial charge extraction with a novel 2D transition metal dichalcogenide ReSe2, the hole‐free CsPbBr3 PSC achieves a champion efficiency of 10.67% with an impressive open‐circuit voltage of 1.622 V and an excellent long‐term stability. This work provides an in‐depth understanding on the precise Cs‐Pb‐Br perovskite phase control and the effect of derivatives on photovoltaic performance of advanced CsPbBr3 PSCs. Abstract : Based on theoretically calculated Gibbs free energies (∆ G ) of Cs‐Pb‐Br derivatives, the 0D Cs4 PbBr6 phase is suppressed by optimizing the fabrication method, delivering a champion efficiency of 10.67% for all‐inorganic CsPbBr3 PSC.